To complete the table of values for the function \( y = x^3 + 1 \), we will calculate \( y \) for each given value of \( x \).
-
For \( x = -3 \): \[ y = (-3)^3 + 1 = -27 + 1 = -26 \]
-
For \( x = -2 \): \[ y = (-2)^3 + 1 = -8 + 1 = -7 \]
-
For \( x = -1 \): \[ y = (-1)^3 + 1 = -1 + 1 = 0 \]
-
For \( x = 0 \): \[ y = 0^3 + 1 = 0 + 1 = 1 \]
-
For \( x = 1 \): \[ y = 1^3 + 1 = 1 + 1 = 2 \]
-
For \( x = 2 \): \[ y = 2^3 + 1 = 8 + 1 = 9 \]
-
For \( x = 3 \): \[ y = 3^3 + 1 = 27 + 1 = 28 \]
The completed table of values is:
| \( x \) | \( y \) | |:---------:|:-----------:| | -3 | -26 | | -2 | -7 | | -1 | 0 | | 0 | 1 | | 1 | 2 | | 2 | 9 | | 3 | 28 |